Internalizing ecological values through green garden innovation at SDN Payungsari II, Karawang - DS, Yulistina Nur; Widiastuti, Hesti; Rahayu, Ade Astuti Widi (Community Empowerment, 2025)
Low environmental awareness and a lack of ecological educational facilities in elementary schools necessitate nature-based innovative solutions. This program aims to enhance environmental stewardship among students at SDN Payungsari II through the development of green school gardens as outdoor learning media. The implementation methods included socialization, simple green technology training, and participatory mentoring. Evaluation results showed significant behavioral shifts: student engagement in plant care rose from 11% to 79%, while the habit of proper waste disposal increased from 35% to 87%. Qualitative data from teacher interviews confirmed an increase in students' responsibility and enthusiasm for environmental conservation. This program demonstrates that green school gardens effectively serve as living laboratories that transform theoretical awareness into sustainable practical habits, fostering ecological character from an early age.